Chemical modifications in solarized soil with addition of organic residues - Cruz, Juliana Cristina Sodário [UNESP]; De Castro Gava, Glauber José; De Almeida Minhoni, Marli Teixeira [UNESP]; De Souza, Nilton Luiz [UNESP]; De AlmeidaSilva, Marcelo; Jeronimo, Elisangela Marques; Padovani, Carlos Roberto [UNESP] (Universidade Estadual de Londrina, 2008)
The soil solarization is used in small properties as an alternative for control of phytopathogens and weeds, besides it also can affect the availability of some nutrients and phytotoxic elements in the soil. Thus, one experiment was carried out as a three-factor factorial (solarized and not solarized soil x with and without addition of vegetable residue x four collection times) for evaluation of variations of pH, organic matter, phosphorus, total nitrogen, potassium, calcium, magnesium and aluminum in a soil characterized as Distrofic Red Latosoil, in Botucatu county (SP). The incorporated vegetable residue was constituted of crop remains of kale (Brassica oleraceae var. acephala L.) fresh and triturated. Soil samples of each treatment were collected from zero to 0.1m of depth, at 7, 21, 35, and 49 days after solarization treatment, from January to March of 2001. Soil chemical analyses were done as well as the soil temperature were monitored on the treatments. The solarized soil with kale organic residues addition treatment presented higher values of pH, organic matter, total nitrogen, phosphorus, potassium, calcium, magnesium and minor values of aluminum.
Modificações químicas em solo solarizado, com e sem incorporação de resíduos orgânicos
Keywords: Alternative control; Fertility of soil; Organic matter